Blood Pressure Changes During Mechanical Thrombectomy for Acute Ischemic Stroke Are Associated With Serious Early Treatment Complications: Symptomatic Intracerebral Hemorrhage and Malignant Brain Edema - Wiącek, Marcin; Szymański, Maciej; Walewska, Klaudia; Bartosik-Psujek, Halina (Frontiers in Neurology, 2022)
Background Symptomatic intracranial hemorrhage (sICH) and malignant brain edema (MBE) are well-known deleterious endovascular treatment (EVT) complications that some studies found to be associated with postprocedural blood pressure (BP) variability. We aimed to evaluate their association with periprocedural BP changes, including its intraprocedural decrease. Methods We retrospectively analyzed the data of 132 consecutive patients that underwent EVT between 1 December 2018 and 31 December 2019, for anterior circulation ischemic stroke. Analyzed predictors of sICH and MBE included non-invasively obtained BP before and 5-min after treatment, intraprocedural relative decreases of BP from baseline, and its post-treatment increases. SICH was defined in accordance with the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (SITS-MOST) criteria and MBE as brain edema with midline shift on the follow-up imaging. We used binary logistic regression analysis to investigate the association of BP parameters and the incidence of sICH and MBE. Results Among the included patients, 11 (8.3%) developed sICH and 31 (23.5%) MBE. The intraprocedural decrease of mean arterial blood pressure (MAP) was independently associated with MBE occurrence (aOR per 10 mmHg drop from baseline 1.27; 95% CI 1.01–1.60; P = 0.040). Over 40% MAP drop was associated with a higher risk of sICH in the entire cohort (aOR 4.24; 95% CI 1.33–13.51; P = 0.015), but not in the subgroup with successful reperfusion (aOR 2.81; 95% CI 0.64–12.23; P = 0.169). Post-treatment systolic blood pressure (SBP) and MAP elevation above their minimal values during MT are significantly associated with the development of sICH (aOR per 10 mmHg SBP increase 1.78; 95% CI 1.15–2.76; P = 0.010 and aOR per 10 mmHg MAP increase 1.78; 95% CI 1.04–3.03; P = 0.035). Conclusions In the anterior circulation ischemic stroke patients relative MAP decrease during EVT is associated with a higher risk of MBE occurrence, and over 40% MAP drop with a higher incidence of both MBE and sICH. Post-treatment elevation of SBP and MAP increased the risk of sICH.